2003
DOI: 10.1128/jvi.77.1.45-56.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Major Apoptotic Pathway Activated and Suppressed by Poliovirus

Abstract: Cells respond to poliovirus infection by switching on the apoptotic program, implementation of which is usually suppressed by viral antiapoptotic functions. We show here that poliovirus infection of HeLa cells or derivatives of MCF-7 cells was accompanied by the efflux of cytochrome c from mitochondria. This efflux occurred during both abortive infection (e.g., interrupted by guanidine-HCl and ending with apoptosis) and productive infection (leading to cytopathic effect). The former type of infection, but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 80 publications
6
76
0
Order By: Relevance
“…4 Effective replication of even the smallest mammalian RNA-containing viruses with very short life cycles, such as poliovirus (7-9 h), appeared to depend on the suppression of apoptosis. [5][6][7] We recently demonstrated that one of the mechanisms of apoptosis suppression during poliovirus infection involves rapid disappearance of a number of short-living receptors from the cell surface, including those for TNF, TRAIL and interferon, 8 making the infected cells less sensitive to these cytokines. This poliovirus function is exerted, at least in part, through 3A, a multifunctional viral protein that is involved in poliovirus RNA replication, 9 virus-induced rearrangement of cytoplasmic membrane structures, 10 and suppression of protein trafficking between the endoplasmic reticulum (ER) and Golgi apparatus, 11,12 an essential step in plasma membrane and secreted protein processing.…”
Section: Introductionmentioning
confidence: 99%
“…4 Effective replication of even the smallest mammalian RNA-containing viruses with very short life cycles, such as poliovirus (7-9 h), appeared to depend on the suppression of apoptosis. [5][6][7] We recently demonstrated that one of the mechanisms of apoptosis suppression during poliovirus infection involves rapid disappearance of a number of short-living receptors from the cell surface, including those for TNF, TRAIL and interferon, 8 making the infected cells less sensitive to these cytokines. This poliovirus function is exerted, at least in part, through 3A, a multifunctional viral protein that is involved in poliovirus RNA replication, 9 virus-induced rearrangement of cytoplasmic membrane structures, 10 and suppression of protein trafficking between the endoplasmic reticulum (ER) and Golgi apparatus, 11,12 an essential step in plasma membrane and secreted protein processing.…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported by our group (Autret et al, 2007(Autret et al, , 2008Brisac et al, 2010) and by Agol's group (Agol et al, 2000;Belov et al, 2003), several series of events may be involved in the regulation of PV-induced apoptosis. The results presented here highlight a new pathway, the CREB/ Herp pathway, which plays an anti-apoptotic role.…”
Section: Herpmentioning
confidence: 56%
“…The induction of apoptosis during PV infection is controlled by a balance between survival pathways early in infection, allowing completion of the viral cycle, and the progression to programmed cell death later in infection (Agol et al, 2000;Autret et al, 2008;Belov et al, 2003). In this study, we showed that the CREB3/Herp signalling pathway was involved in modulating this balanced regulation.…”
Section: Herpmentioning
confidence: 69%
See 1 more Smart Citation
“…Second, MDA5 is degraded in PV-infected cells in a proteasome-and caspase-dependent manner, resulting in the lack of type I IFN production (29). Third, PV-mediated apoptosis occurs in a caspase-dependent manner to disable infected cells from inducing an IFN response (46), with the MDA5-dependent innate response to PV infection becoming minimal within 3 h postinfection. Additionally, RIG-I is also cleaved by the viral protease 3C (47), and additional RIG-I functions are subsequently disrupted.…”
Section: Discussionmentioning
confidence: 99%